2006
DOI: 10.1007/s11434-006-2047-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a nitrogenase CrFe protein from a mutant UW3 of Azotobacter vinelandii grown on a Cr-containing medium

Abstract: Through the anoxic chromatography on the columns of DEAE-52, Q-Sepharose and Sephacryl S-200, a CrFe protein preparation was obtained from UW3, a mutant of Azotobacter vinelandii, which grew well on the Cr-containing medium. Compared with MoFe protein (OP Av1) from wild-type strain OP, ~50% protein in the preparation had similar subunits composition and had immune reaction with antibody of OP Av1. The preparation had ~40% of C 2 H 2 −, H + -and N 2 (expressed by the difference in H + -reduction activity betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was proved by immunoblotting that both CrFe protein (Zhang et al 2006) and MnFe protein (unpublished) also have immune reaction with antibody to MoFe protein. Metal analysis showed that the partially purified CrFe and MnFe proteins contain not only Fe, but also Cr and Mn, respectively, although smaller amounts of Mo had been detected (Huang et al 2001b(Huang et al , 2002.…”
Section: Synthesis In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…It was proved by immunoblotting that both CrFe protein (Zhang et al 2006) and MnFe protein (unpublished) also have immune reaction with antibody to MoFe protein. Metal analysis showed that the partially purified CrFe and MnFe proteins contain not only Fe, but also Cr and Mn, respectively, although smaller amounts of Mo had been detected (Huang et al 2001b(Huang et al , 2002.…”
Section: Synthesis In Vivomentioning
confidence: 99%
“…In addition, our EPR results have shown that the EPR spectra of the CrFe and MnFe proteins are different from that of the MoFe protein as well as each other, indicating that they have their own different EPR characteristics. Based on calculation of the signal intensity to Cr, Mn, and Mo contents using the method of Yousafzai et al (1996), the EPR signal intensity ratio of CrFe protein to wildtype MoFe protein was 83%, 0%, and 40% (Zhang et al 2006) at g = 4.3, 3.7, and 2.01, respectively, whereas the corresponding ratios for the MnFe protein were 235%, 113%, and 143% (unpublished). It is worth noting that the CrFe protein has no EPR signal at the g = 3.7 region, whereas the MnFe protein has a similar intensity to that of the MoFe protein at this region.…”
Section: Synthesis In Vivomentioning
confidence: 99%
“…nifUSVWZ and nifM are used in biosynthesis of all three enzymes. Recently, a new nitrogenase CrFe protein was obtaind from a mutant of A. vinelandii grown on Cr-containing medium (Zhigang, 2006).…”
Section: Figure (1-6): Azotobacter Vinelandii Cellmentioning
confidence: 99%